The Principle of Efficiency in the Fight Against Corruption in Brazil (Revista do CAAP, 2018)
This article aims to analyze the principle of efficiency, present in article 37 of the Brazilian Constitution, for its potentiality to be a constructive factor in the fight against corrupt practices in the country. It first tries to give a brief overview of the history of the principle, how it came to be what it is and how it differentiates from the mere concept of efficiency, by way of historical analysis and studies regarding the importance of principles in Brazilian law. Then, it contextualizes corruption as an important factor in the Brazilian society, and proposes to set light to the link of causation between corruption and inefficiency in the public field, by setting a role, or duty, of the Administration to maintain great quality of the services it provides. After, it sets three proposals of ways which the Administration could use to improve its ability to fulfill that role. Keywords: Principle of efficiency; Efficiency; Corruption; Public Administration.